Low-temperature, inkjet printed p-type copper(i) iodide thin film transistors. Issue 43 (24th October 2016) - Choi, Chang-Ho; Gorecki, Jenna Y.; Fang, Zhen; Allen, Marshall; Li, Shujie; Lin, Liang-Yu; Cheng, Chun-Cheng; Chang, Chih-Hung
Abstract : Low temperature fabrication of printed p-type CuI TFTs was reported for the first time. Abstract : Low temperature fabrication of printed p-type CuI TFTs was reported for the first time. The printed CuI film was fabricated by printing molecular CuI ink directly onto the device substrate followed by immediate crystallization of CuI nanoparticles as the solvent evaporated. The substrate temperature during inkjet printing was varied in order to obtain continuous CuI films with large grain size for improved device performance. The CuI TFTs printed at 60 °C exhibited an average field-effect mobility of 1.86 ± 1.6 cm 2 V −1 s −1, with the maximum value of 4.4 cm 2 V −1 s −1 and an average On/Off ratio of 10 1 –10 2 . This study demonstrates potential low temperature, directly printed p-type TFTs for constructing transparent, complementary inorganic TFT circuits.